Being in the world - Ruspoli, Tao (New York : Kino Lorber, 2011)
Being in the World raises the question of whether we have forgotten what it means to be truly human in today's technological age, and this program proceeds to answer this question by taking a journey around the world to meet a whole host of remarkable individuals, including Manuel Molina, the legendary poet and flamenco master; Leah Chase, affectionately known as the Queen of Creole Cuisine; and Hiroshi Sakaguchi, a master carpenter from Japan. While we watch them work and struggle to introspect and talk about their art and their craft, we also hear Hubert Dreyfus and his students reflect on Heidegger and his philosophy. Our artisans confess that they cannot explain in rational terms how they do what they do. The being is in the doing. Interviews and action intertwine to make a challenging philosophy clear to the lay viewer.
English or Spanish dialogue; Spanish or English subtitles.
film